Effects of Polyherbal Tablet for Hypertensive Patients - Woro Rukmi Pratiwi; Eti Nurwening Sholikhah; Dwi Aris Agung Nugrahaningsih; Mia Munawaroh Yuniyanti; Mustofa Mustofa; Setyo Purwono (Faculty of Pharmacy, Universitas Gadjah Mada, 2020)
Hypertension is a degenerative disease whose prevalence is high and continues to increase over time. Polyherbal tablet have long been used by Indonesian people for hypertension drugs containing garlic (Alium sativum), jelawe (Belericae fructus), temu ireng rhizomes (Curcumae aeruginosae) and kapulaga (Amomi fructus) extracts. This study aims to determine the effect of polyherbal tablet on hypertensive patients. The subjects of 29 hypertensive patients participated in a open-randomized-without comparison-study for 6 weeks. Subjects were divided into 3 groups, each subject received polyherbal tablet with a dose of 2x600 mg (group 1), 2x1200 mg (group 2) and 2x2400 mg (group 3). Blood pressure was monitored on D-0, D-3, D-5, D-7, W-2, W-3, W-4, W-5 and W-6. There was a significant decrease in systolic and diastolic blood pressure at the sixth week in all three treatment groups. The highest decrease in systolic blood pressure was in group 1 while diastolic blood pressure was in group 2 (-22.94 ± 5.871 and 13.13 ± 4.324 respectively). The lowest reduction in systolic and diastolic blood pressure occurred in the third group (-15.07 ± 3,519 and 8.98 ± 3,394 respectively). This study suggests that polyherbal tablet contains garlic (Alii sativi), jelawe (Belericae Fructus), temu ireng rhizome (Curcumae aeruginosae) and cardamom (Amomi Fructus) can reduce blood pressure in patients with hypertension.